Complexity of visual learning material moderates the effects of instructor's beat gestures and head nods in video lectures. (February 2022) - Pi, Zhongling; Zhu, Fangfang; Zhang, Yi; Chen, Louqi; Yang, Jiumin
Abstract: Instructors often show rhythmic movements with speech in video lectures. However, the effects of these movements have not been tested in video lectures with an instructor and visual learning material. Results of Experiment 1 showed students in the beat gestures and head nods conditions showed significantly less attention to the visual learning material, more attention to the instructor, whereas in the beat gestures + head nods condition drew significantly more attention to both. In Experiment 2 we tested whether the complexity of the visual learning material moderated the effects of rhythmic movements on students' learning. When the presentation was simple, students in the head nods + beat gestures condition showed more positive interaction, and significantly better recall and transfer. The results have implications for video designing: if an instructor and simple learning material are visible, she is encouraged to show beat gestures and head nods to mark important information. Highlights: An instructor's rhythmic movements affected students' attention allocation. Rhythmic movements facilitated learning from the videos with simple material. Rhythmic movements had no benefits in the videos with complex material.